La postérité des Noces Chymiques dans la littérature théosophique et anthroposophique - Aurélie Choné (Recherches Germaniques)
The Theosophical Society, founded in New York in 1875, includes a Rosicrucian current that sees the Rosy Cross as ‘the divine light of self-knowledge’ (Franz Hartmann, 1838-1912). Yet there are no commentaries specifically dedicated to the Chymical Wedding in the theosophical literature. Like Helena Blavatsky (1831-1891), the co-founder of the Theosophical Society, the Austrian theosopher Rudolf Steiner (1861-1925) was convinced that the mysteries of the Rosy Cross were ‘solely passed on through oral tradition’ (1906). Steiner became the Secretary General of the German branch of the Theosophical Society in 1902. He expected to discover authentic Rosicrucian rituals when he joined the Freemasons as his mentor Goethe had. But like the theosophers, he observed that the true spirit of the Rosy Cross was no longer to be found in the secret societies of his day. In 1906, the ‘Rosy Cross of the Theosophical Society’ began presenting the ‘Mystery of Golgotha’ as an entirely unique event in the history of mankind, at odds with the Theosophical Society’s custom of granting equal importance to all religions. In 1917, ten years after leaving Annie Besant’s Esoteric School and five years after founding the Anthroposophical Society, Steiner published a study on the Chymical Wedding in Berlin. The present article shows that this written commentary was a means for him to situate himself in the continuity of the Rosicrucian tradition of esoteric Christianity while introducing his own theosophy, which he called ‘anthroposophy’ or ‘spiritual science’, as the heir of the authentic Rosicrucians. The reference to the authoritative text allowed him to illustrate and justify his former assertions on 1) the actual existence of Christian Rosenkreuz and the Rosicrucian order, 2) the seven stages of Rosicrucian initiation, 3) Rosicrucianism as the best way of initiation for modern European man, 4) the “etheric vision” of Christ based on the action of Christian Rosencreuz’s “etheric body”. These ideas influenced a number of Western esotericists, including Neville Meakin (†1912), Max Heindel (1865-1919) and Jan van Rijckenborgh (1896-1968).